Preparation of Mixed Matrix Membranes Containing ZIF-8 and UiO-66 for Multicomponent Light Gas Separation - Eun Young Kim; Hyun Su Kim; Donghwi Kim; Jinsoo Kim; Pyung Soo Lee (Crystals, 2018)
Mixed matrix membranes (MMMs) containing zeolitic imidazolite framework-8 (ZIF-8) and UiO-66 as microporous fillers were prepared and evaluated their potential for the separation of a gas mixture produced by a methane reforming process. Hydrothermal synthesis was performed to prepare both the ZIF-8 and UiO-66 crystals, with crystal sizes ranging from 50 to 70 nm for ZIF-8 and from 200 to 300 nm for UiO-66. MMMs were prepared with 15% filler loading for both MMM (ZIF-8) and MMM (UiO-66). MMM (UiO-66) exhibited H2 permeability of 64.4 barrer and H2/CH4 selectivity of 153.3 for single gas permeation, which are more than twice the values that were exhibited by a neat polymer membrane. MMM (ZIF-8) also showed better separation properties than that of a neat polymer membrane with H2 permeability of 27.1 barrer and H2/CH4 selectivity of 123.2. When a gas mixture consisting of 78% Ar/18% H2/4% CH4 flowed into the membranes at 5 bar, the H2 purity increased to as high as 93%. However, no improvement in the mixture gas separation performance was achieved by the MMMs as compared to that of a neat polymer membrane.